THE INFLUENCE OF PACKAGING DESIGN, BRAND IMAGE AND SERVICE QUALITY ON CONSUMER PURCHASE INTENTION (CASE STUDY: UNIVERSITY STUDENT CUSTOMERS OF MAXX COFFE MANADO) - Bajang, Bryan P. (Jurnal Berkala Ilmiah Efisiensi, 2016)
What makes all the coffee shops different are the marketing strategy, brand image and service quality. Package design is how creative and innovative the company to design the package of the product to get attention of the consumer. Brand image is the current view of the customers about the brand it self, meanwhile service quality is an assessment of how well the delivered service conforms to the customers expectation. The aims of this research is to know if there is a influence of packaging design, brand image, and service quality toward consumer purchase intention. This research used a multiple linear regression analysis The result from this research shown that the Packaging Design and service quality have significantly influence consumer purchase intention to university student in Manado City to purchase the products. Brand image is not significantly influence. Most of universityÂ  student really think about the product price and the location of the cafe which mean its easier to reach. The consumer also pay an attention on the sevice at Maxx Coffee Manado, which is the employeesâ€™ attitude, how good they served the consumer, and how they make the consumer want to stay at Maxx Coffee longer.